2015
DOI: 10.1002/14651858.cd010856.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Water fluoridation for the prevention of dental caries

Abstract: There is very little contemporary evidence, meeting the review's inclusion criteria, that has evaluated the effectiveness of water fluoridation for the prevention of caries.The available data come predominantly from studies conducted prior to 1975, and indicate that water fluoridation is effective at reducing caries levels in both deciduous and permanent dentition in children. Our confidence in the size of the effect estimates is limited by the observational nature of the study designs, the high risk of bias w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
203
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(278 citation statements)
references
References 213 publications
4
203
0
12
Order By: Relevance
“…38 More recently, a Cochrane review of water fluoridation has been published. 39 The included studies suggest that water fluoridation results in a 35% reduction in decayed, missing or filled primary teeth and a 26% reduction in decayed, missing or filled permanent teeth. However, the review team queried the applicability of these findings to current populations, as the majority of the studies included in the review were conducted before fluoride toothpastes and other preventative measures were widely introduced.…”
Section: Water Fluoridationmentioning
confidence: 99%
See 1 more Smart Citation
“…38 More recently, a Cochrane review of water fluoridation has been published. 39 The included studies suggest that water fluoridation results in a 35% reduction in decayed, missing or filled primary teeth and a 26% reduction in decayed, missing or filled permanent teeth. However, the review team queried the applicability of these findings to current populations, as the majority of the studies included in the review were conducted before fluoride toothpastes and other preventative measures were widely introduced.…”
Section: Water Fluoridationmentioning
confidence: 99%
“…However, the review team queried the applicability of these findings to current populations, as the majority of the studies included in the review were conducted before fluoride toothpastes and other preventative measures were widely introduced. Iheozor-Ejiofor et al 39 reported that over 97% of the 155 studies included in the review were at a considerable risk of bias and concluded that the evidence for the effectiveness of water fluoridation is limited because of the considerable risk of bias within the studies and substantial between-study variation. In the UK, the NIHR has commissioned an evaluation of the cost, and effects, of water fluoridation in the contemporary context.…”
Section: Water Fluoridationmentioning
confidence: 99%
“…A eficácia da fluoretação já foi há muito comprovada, e revisões sistemáticas confirmam este fato: a pesquisa de McDonalgh et al 15 evidenciou que em regiões fluoretadas havia um número maior de crianças sem cárie em comparação com áreas não fluoretadas; a revisão sistemática de IheozorEjiofor, que objetivou foi analisar os efeitos da fluoretação na prevenção da cárie e também nos riscos de se desenvolver de fluorose dentária, comprovou que a medida é eficaz na redução dos níveis de cárie na dentição decídua e permanente em crianças 16 .…”
Section: Discussionunclassified
“…More recently data from case reporting has become the cornerstone of monitoring and evaluating national and worldwide progress to elimination of HIV (WHO, 2015a). A second group of mandatory public health activities is mass screening, treatment or preventive supplementation, the latter including the addition of fl uoride to drinking water (Iheozor-Ejiofor et al, 2015), iodide to salt or vitamins to cereal grains (Raitiainen et al, 2016); a prominent example is the decision to supplement cereal grains consumed by pregnant women with folic acid to prevent neural tube defects in foetuses (Ray et al, 2002). Mass drug administration may also be done at the individual level, such as administration of topical antibiotics to all newborns to presumptively treat gonococcal ophthalmia and parenteral vitamin K to prevent neonatal haemorrhage (Zi-pursky, 1999).…”
Section: Parallels To Other Communicable Disease Control Programmesmentioning
confidence: 99%